Quadriceps Crush Contusion in Athletes: The Effectiveness of Orthobiologic Treatment with Platet-Rich Plasma (PRP) - Korta, Karolina; Bieńko, Marta; Marchaj, Magdalena; Bieńko, Mateusz; Putra, Anna; Król, Tomasz; Toborek, Michalina; Niedziela, Natalia; Maciąg, Maria; Bednarz, Karolina (Quality in Sport, 2024)
Introduction: Quadriceps contusion is a common injury in contact sports like football, rugby, and basketball, resulting from a direct blow to the anterior thigh. This causes muscle damage, bleeding, and inflammation. While often considered minor, poor management can lead to complications, delayed recovery, and impaired athletic performance. Purpose: The purpose of this review is to evaluate the effectiveness and the role of orthobiologic treatments such as PRP in enhancing healing and functional recovery for a swift return to sport. Summary: Quadriceps contusion, resulting from direct trauma to the quadriceps muscle group, leads to hematoma formation and varying degrees of injury severity. Diagnosis is primarily clinical, often supported by ultrasound and MRI to assess the extent of muscle damage. Treatment is typically non-operative, involving rest, ice, compression, physical therapy, and a gradual return to activity. One significant complication is myositis ossificans, characterized by abnormal bone formation within the muscle, which can cause chronic pain and restricted movement. Recent advances, such as ultrasound-guided PRP injections, offer promising results by enhancing healing, relieving pain, and accelerating functional recovery. PRP therapy, particularly popular among athletes, promotes tissue repair by stimulating cell regeneration and reducing inflammation, helping speed up recovery and potentially lowering the risk of complications like myositis ossificans. Although preliminary evidence supports the effectiveness of PRP in helping athletes return to play sooner, more research is needed to validate its full impact on musculoskeletal injuries. Continued exploration of nonoperative treatment and rehabilitation protocols is also necessary to ensure optimal outcomes. Preventive strategies, including the use of protective gear and conditioning exercises to strengthen muscles, are critical in reducing the risk of injury and enhancing athletic performance.